2004
DOI: 10.2320/matertrans.45.9
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Gas-Vacancy-Complexes in Fe Irradiated with High Energy H or He Ions

Abstract: Isochronal annealing experiments for Fe irradiated with H or He ions were carried out to study interactions between gas atoms and vacancy clusters. The accelerating energy of H and He ions was 1.0 MeV and 3.3 MeV, respectively. The total dose was 1:0 Â 10 21 H ions/m 2 (0.2 dpa) and 9:6 Â 1019 He ions/m 2 (0.3 dpa), and the irradiation temperature was 300 C. Positron annihilation lifetime and coincidence Doppler broadening (CDB) measurements were carried out after irradiation and annealing for 1 hour up to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Experimentally, nuclear reaction depth profiling [13], transmission electron microscopy [14], positron annihilation lifetime and coincidence Doppler broadening (CDB) techniques [15,16] have been used in addition to THDS [10,17,18] to study He migration and He-induced defect clusters in iron. In addition, resistivity recovery measurement has been used to study kinetics of defects in iron produced by electron irradiation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, nuclear reaction depth profiling [13], transmission electron microscopy [14], positron annihilation lifetime and coincidence Doppler broadening (CDB) techniques [15,16] have been used in addition to THDS [10,17,18] to study He migration and He-induced defect clusters in iron. In addition, resistivity recovery measurement has been used to study kinetics of defects in iron produced by electron irradiation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Positrons from Na-22 in metals with many defects do not migrate as long as in well-annealed metals. Therefore, it is even possible to measure the lifetime of defects distributed within 10 lm from the surface [13]. The lifetimes measured from the two surfaces were nearly the same, which indicated that the cavitation damage formed not only near the impact surface, but rather was homogeneously distributed over the 0.1-mm-thick specimen.…”
Section: Nickelmentioning
confidence: 93%
“…High purity (99.94%) SC iron disks were provided by Dr S.A. Maloy at Los Alamos National Laboratory. Small specimens ($0.5-1 Â 2.5 Â 3.5 mm) were cut from the plates or disks, mechanically polished to 1 lm grade smoothness, and then commercially implanted at room temperature with 4 He ions at 5 or 10 keV to fluences of 10 14 or 10 15 He/cm 2 . The implantation flux was $7-10 Â 10 10 He/cm 2 s. Grain size of the PC specimens was determined to be on the order of 50 lm through optical microscopy observations.…”
Section: Methodsmentioning
confidence: 99%
“…On the average, 20 and 33 Frenkel pairs are generated per He ion for the two energies, respectively. These values correspond to a peak displacement damage of $85 and 75 mdpa, and a peak He concentration of 2830 and 1760 appm for the two energies, respectively, at a fluence of 10 15 He/cm 2 .…”
Section: Trim/srim Calculationsmentioning
confidence: 97%
See 1 more Smart Citation